Theoretical selection criteria of organic Rankine cycle form for different heat sources. (1st January 2022) - Hui-Xing, Zhai; Wei, Dong; Lin, Shi; Qing-Song, An; Sui-Lin, Wang; Bao-Lin, An
Abstract: Organic Rankine cycle (ORC) is an effective way for low to medium grade heat to power conversion. A suitable cycle form (subcritical or trans -critical, whether to use a regenerator) is the guarantee of good cycle performance. The selection of cycle forms strongly depends on the heat source conditions. In this work, the heat source types and ORC forms are introduced firstly. Then the cycle form selection criteria are obtained through theoretical derivation, directly from the heat source parameters and getting rid of the working fluid properties, thus, having more universal applicability. The main criteria include: when T hs, out > T hs, in + Δ T p + T cd 2 ( T hs, out is the outlet temperature of the heat source, T hs, in is the inlet temperature of the heat source, Δ T p is the pinch temperature difference between the heat source and the working fluid, T cd is the working fluid condensation temperature), subcritical ORC has better thermodynamic performance than trans -critical cycle; when T hs, out > 2 T hs, in + Δ T p + T cd 3, a regenerator is needed to improve the cycle performance. At last, simulation results of 35 working fluids for four typical heat sources are used to verify the theoretical criteria. Highlights: Criteria are given to determine the ORC form for different heat sources. ORC form selection criteria are originally obtained through theoretical derivation. Theoretical ORC form selection criteria are of universal applicability. Criteria are verified with results of typical heat sources and 35 working fluids.